Prosedur Registrasi Online Pertunjukan Perempuan-Perempuan Pilihan Oleh PT Kayangan Abadi Andalan - Mutia Nanda Darmawan; Etty Kongrat (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
Registration is one of the important elements in organizing a show because registration will be the audience's first impression of the show being held. This study discusses the pre-registration and re-registration procedures as well as the obstacles and solutions that were given during registration in the Pre-Selected Women fight. The purpose of this research is to find out the pre-registration and re-registration procedures as well as to find out the obstacles and solutions that were made during the registration. Methods of data collection in this study using the method of observation and computational methods. Methods of data analysis using procedural descriptive qualitative analysis, in which data processing is done by describing the data in the form of regular, coherent, logical, and effective sentences. The results of the study show that registration for the Preferred Women's Show, namely: one, pre-registration which starts with preparing the caket.org platform, prospective viewers register via the caket.org platform, until the prospective audience gets an e-ticket; two, re-registration, the audience shows their e-ticket to the registration staff and the registration staff will scan the barcode to check the data. Keywords: Performance, Pre-Registration, Re-registration